Generation of Blastocyst-like Structures from Mouse Embryonic and Adult Cell Cultures - Li, Ronghui; Zhong, Cuiqing; Yu, Yang; Liu, Haisong; Sakurai, Masahiro; Yu, Leqian; Min, Zheying; Shi, Lei; Wei, Yulei; Takahashi, Yuta; Liao, Hsin-Kai; Qiao, Jie; et al. (Cell, 2019)
A single mouse blastomere from an embryo until the 8-cell stage can generate an entire blastocyst. Whether laboratory-cultured cells retain a similar generative capacity remains unknown. Starting from a single stem cell type, extended pluripotent stem (EPS) cells, we established a 3D differentiation system that enabled the generation of blastocyst-like structures (EPS-blastoids) through lineage segregation and self-organization. EPS-blastoids resembled blastocysts in morphology and cell-lineage allocation and recapitulated key morphogenetic events during preimplantation and early postimplantation development in vitro. Upon transfer, some EPS-blastoids underwent implantation, induced decidualization, and generated live, albeit disorganized, tissues in utero. Single-cell and bulk RNA-sequencing analysis revealed that EPS-blastoids contained all three blastocyst cell lineages and shared transcriptional similarity with natural blastocysts. We also provide proof of concept that EPS-blastoids can be generated from adult cells via cellular reprogramming. EPS-blastoids provide a unique platform for studying early embryogenesis and pave the way to creating viable synthetic embryos by using cultured cells.